ANALISIS WACANA KRITIS (AWK) DALAM CERPEN DUA SAHABAT KARYA BUDI DARMA: KONTEKS PEMBELAJARAN BAHASA DAN SASTRA INDONESIA - Mustofa (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
Literary texts can be analysed by using critical discourse analysis (CDA). CDA is a type of analysis that can be used to reveal ideology, Power, political view and gender. In here, CDA is used to reveal ideology and Power within the language used by Budi Darma in his Dua Sahabat Short story. This study can be relevant to the context of language and literature learning at schools. It is interesting to be done because learners must be able to understand the language of ideology and power, which has indirect influence but has also significant impact to learners’ opinions on ideology and power. Every discourse related to ideology and power always contain prejudice because within the discourse there are language expressions with symbolic meanings or because the word choices need to be interpreted whether it contains positive or negative things.